PENGARUH SUPLEMENTASI HIDROLISAT BULU AYAM DAN MINERAL ORGANIK UNTUK MENINGKATKAN KECERNAAN PROTEIN KASAR PADA RANSUM SAPI - Rahdian Martha Wijaya; Muhtarudin .; Rudy Sutrisna (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
This study aims to optimize the utilization of agro-industry waste through supplementation ofhydrolyzed chicken feather and organic minerals in the ration as an effort to improve the digestibilityof crude protein and crude fiber in ruminant. This study used 3 beef cows. The experimental designused is a Latin square design 3x3 with 3 cows as a rows and 3 periods as columns. The treatmentgiven is R0: basal diet (30% + 70% forage concentrate) ; R1: basal diet + 3% hydrolyzed chickenfeathers ; R2: organic macro mineral (0.5% organic Ca, Mg 0.04% organic) and organic microminerals (40 ppm organic Zn, 10 ppm Cu organic, organic Se 0.10 ppm, and 0.30 ppm of organic Cr).The data obtained were tested by analysis of variance. The results showed that the effect of theaddition of hydrolyzate chicken feathers 3% NaOH and organic macro and micro minerals in the dietwas not significantly different (P> 0.05) on the digestibility of protein and crude fiber in the ration ofcattle rations.